2019
DOI: 10.4103/jcd.jcd_195_19
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of polyacrylic acid-bioactive glass air abrasion preconditioning with NovaMin remineralization on the microhardness of incipient enamel-like lesion

Abstract: Background: Bioactive glass (BAG) remineralization is a promising method for dental hard tissue regeneration. The aim of this study was to evaluate the microhardness of incipient enamel-like lesions with or without preconditioning by air abrasion using polyacrylic acid (PAA)-BAG before application of NovaMin remineralizing agent. Materials and Methods: Forty extracted human molars were selected, sectioned mesiodistally obtaining buccal and lingual halves, and embedded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The results of this study is in agreement with Alafifi et al (21) who found that using Nano-hydroxyapatite has the ability to occlude the opened dentinal tubules because of the size of the nanoparticles which was smaller than the size of the dentinal tubules, it is possible that the carbonated apatite nanoparticles adhered to opened dentinal tubules. In addition, the nano-sized particles have an affinity and can induce deposition on irregular spaces (22) .…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study is in agreement with Alafifi et al (21) who found that using Nano-hydroxyapatite has the ability to occlude the opened dentinal tubules because of the size of the nanoparticles which was smaller than the size of the dentinal tubules, it is possible that the carbonated apatite nanoparticles adhered to opened dentinal tubules. In addition, the nano-sized particles have an affinity and can induce deposition on irregular spaces (22) .…”
Section: Discussionsupporting
confidence: 92%
“…In both scores, the structural integrity of the enamel is maintained and intact with no localized breakdown. When these lesions are left untreated, they might progress to a continuous loss of minerals and break down until cavitation 2 . Current cariology research focused on the effectiveness of the application of some remineralizing agents that maintained ion supersaturation in the oral environment surrounding these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In calcium / phosphorous ratio MI Paste decreased with (-0.52 ± 0.26) and MI Paste Plus decreased with (-0.55 ± 0.05). Comparison between both groups was performed by using independent t-test revealed insignificant difference between them as P<0.05, as presented in table (2) and figure (6).…”
Section: Evaluation Of Calcium Phosphorous and Calcium / Phosphorous ...mentioning
confidence: 99%
“…In calcium / phosphorous ratio MI Paste increased with (0.37 ± 0.14) and MI Paste Plus decreased with (0.57 ± 0.01). Comparison between both groups was performed by using Independent t-test revealed significant difference between them as P < 0.05 (MI Paste Plus was significantly higher than MI Paste in calcium, phosphorous and calcium / phosphorous ratio), as presented in table (2) and figure (6).…”
Section: Demineralization-reminerlization Changesmentioning
confidence: 99%
See 1 more Smart Citation